Pendidikan Islam Perspektif Pesantren: Diferensiasi, Aplikasi dan Motivasi - Jasminto (Fakultas Agama Islam, Universitas Hasyim Asy'ari, 2020)
This article discusses several definitions of Islamic education and gives guidelines to clarify the use of the definition. The article describes that the definition depicts the typology of Islamic education and institutions related to it. This will explain the different concepts that depend on the context of Islamic education, especially with regard to pondok pesantren. Later, the article elucidates the theoretical conception of Islamic education based on the Qur’an and hadith. This article argues that the primary motivation of the holistic approach of ‘Islamic education’ of pesantren can be used as the representative of Islamic education in the world that teaches religious moderation.